Ocenjevanje in poučevanje nekaterih atletskih elementov - Železnik Mežan, Lea (Šport (Ljubljana), 2024)
The aim of the study was to validate the rating scales for the shot put and hurdles and to compare students’ knowledge of these two tests and with their self-assessments of athletics knowledge. 76 students from the Faculty of Sport who are taking Athletics 1 were included. Their athletic knowledge was videotaped and then assessed using newly developed scales and descriptions. The shot put was assessed by three assessors and the hurdles by four assessors – athletics assistants and experienced athletics coaches. The students’ self-assessments of athletic knowledge and their self-reports of their previous experience of athletics were analysed using a questionnaire. To analyse the congruence of the assessments, we used Interclass Correlation Coefficients. The correlation between the different variables was calculated using the Spearman coefficient. We found a good agreement between different raters, which was even better for shot put (?=0.836 vs. ?=0.744). We found that only 15% of students were familiarised with hurdling in primary or secondary school as it is not part of the curriculum. Nevertheless, their knowledge of hurdling was rated higher (2.57) than that of shot put (1.98). Hurdling is an interesting athletics discipline that should be included in the primary and secondary school curriculum.
Keywords: descriptions; hurdling; merila; objectivity; objektivnost; opisniki; scales; shot put; sport; sunek težke žoge; šport; tek čez ovire